Colored asphalt ultrathin wearing layer and preparation method thereof

By using components such as ceramic particles, grafted modified lignin fibers and fluorine modified epoxy resin in the ultra-thin wear layer of colored asphalt, the problem of insufficient bonding strength is solved, higher bonding and anti-slip properties are achieved, and service life is extended.

CN119874257APending Publication Date: 2025-04-25JIANGSU ZENGGUANG COMPOSITE MATERIAL TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510056235.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The bonding strength of the ultra-thin wear layer of colored asphalt is insufficient, resulting in easy peeling and loosening diseases under the influence of traffic loads and environmental factors, shortening the service life.

Method used

Components such as ceramic particles, grafted modified lignin fibers and fluorine modified epoxy resin are used to form a stable bonding structure through the combination of modified decolorization bitumen and compatibility agents, and the bonding strength of the wear layer is enhanced.

Benefits of technology

It significantly improves the bonding and anti-slip properties of the ultra-thin wear layer of colored asphalt, extends the service life, and reduces the occurrence of peeling and delamination.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a colored asphalt ultrathin wearing layer and a preparation method thereof, and relates to the technical field of asphalt, and the colored asphalt ultrathin wearing layer is prepared from the following raw materials in parts by mass: 35-50 parts of ceramic particles, 5-8 parts of toner, 42-60 parts of powder, 6-7 parts of modified decolorized asphalt, 0.5-1.5 parts of compatilizer, 0.5-1.5 parts of diluent and 0.2-0.5 part of plasticizer. The preparation raw materials of the modified decolored asphalt comprise a decolored asphalt body, graft modified lignin fibers and fluorine modified epoxy resin. The preparation method comprises the following steps: stirring and mixing the components to obtain an asphalt mixture; and paving the asphalt mixture on a pavement base layer, and compacting to obtain the colored asphalt ultrathin wearing layer. The wear layer has the effect of improving the adhesion performance, wear resistance and skid resistance of the wear layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of asphalt technology, and in particular to a colored asphalt ultra-thin wear layer and a preparation method thereof. Background Art

[0002] With the acceleration of urbanization, urban roads not only bear the heavy responsibility of transportation, but also become an important part of urban landscape. Although the traditional black asphalt pavement can meet basic transportation needs in terms of function, it is gradually insufficient in terms of aesthetics and diversified needs. Colored asphalt ultra-thin wear layer came into being. With its rich color selection, it can fit various urban landscape design concepts, such as creating characteristic blocks, tourist scenic area roads, etc., adding unique charm to the city. At the same time, in some transportation hubs, such as airports and high-speed rail stations, different colors of wear layers can be used to distinguish lanes and guide traffic, which can greatly improve traffic operation efficiency.

[0003] At present, a large number of existing roads are facing problems such as wear, aging, and decreased anti-skid performance. Conventional road repair methods are often time-consuming and costly, and cause great interference to traffic during construction. The ultra-thin colored asphalt wear layer is easy and fast to construct due to its ultra-thin characteristics. It can be laid in a short time and minimize the impact on traffic flow. Moreover, compared with traditional repair methods, the colored asphalt wear layer can solve multiple needs such as improving the appearance of the road surface, improving anti-skid and wear resistance, etc. at one time, avoiding repeated construction. However, in actual applications, its bonding strength problem has become a key factor restricting further promotion. Once the bonding is not strong, it is very easy to have peeling, looseness and other defects, which greatly shortens the service life, so it needs to be improved. Summary of the invention

[0004] In order to improve the bonding performance of a colored asphalt wear layer, the present application provides a colored asphalt ultra-thin wear layer and a preparation method thereof.

[0005] The present application provides a colored asphalt ultra-thin wear layer and a preparation method thereof using the following technical solutions: In the first aspect, the present application provides a colored asphalt ultra-thin wear layer, which adopts the following technical solution: A colored asphalt ultra-thin wear layer, the raw materials for preparing the same include the following components in parts by weight: Ceramic particles 35-50 parts Color powder 5-8 parts Powder 42-60 parts Modified decolorized asphalt 6-7 parts Compatibilizer 0.5-1.5 parts Diluent 0.5-1.5 parts Plasticizer 0.2-0.5 parts The raw materials for preparing the modified decolorized asphalt include decolorized asphalt body, grafted modified lignin fiber and fluorine-modified epoxy resin.

[0006] Ceramic particles have high hardness and good wear resistance, and are evenly dispersed in the wear layer system. During the friction and rolling process generated by continuous vehicle driving, they effectively bear external force impact, reduce the loss of the main structure of the wear layer, and extend the service life of the road surface; the rough surface of ceramic particles increases the friction between the road surface and the vehicle tires, and the color powder, powder, etc. cooperate with the modified bleached asphalt to form a suitable micro-texture on the surface of the wear layer, which can provide reliable grip for the vehicle in both dry and wet environments, effectively ensure driving safety, and improve the anti-skid performance of the wear layer; the grafted modified lignin fibers in the modified bleached asphalt are closely connected with the bleached asphalt through chemical bonding, physical adsorption, etc., which enhances the cohesion of the asphalt itself, so that the wear layer and the underlying road surface or other contact interfaces form a stable bond, effectively preventing peeling and delamination under the repeated action of traffic loads and environmental factors; fluorine-modified epoxy resin, with its excellent chemical activity, further optimizes the bonding force between asphalt and each component and improves the overall bonding strength.

[0007] Preferably, the raw materials for preparing the compatibilizer include aminosilane coupling agent and linoleic acid.

[0008] The long carbon chain structure of linoleic acid is flexible and hydrophobic. The long carbon chain can interpenetrate and entangle with the organic system better, increase the solubility and dispersibility of silane coupling agent in organic materials such as asphalt, and reduce the interfacial energy between it and organic components. The unsaturated double bond increases the variability of the molecular structure and the adaptability to different environments, and can better adjust the interfacial properties, thereby enhancing the compatibility of silane coupling agent in different systems; the compatibilizer molecule constructed by the reaction of linoleic acid and aminosilane coupling agent can increase the active sites on the molecule, further strengthen the chemical bonding with inorganic and organic substances, and change the interfacial bonding between the wear layer and the base layer from a single-point connection to a multi-point, surface connection, thereby improving the bonding performance; the compatibilizer can promote better dispersion of ceramic particles in the asphalt matrix, make their spacing uniform and their arrangement orderly, and can be evenly stressed when external force acts, avoiding local stress concentration leading to particle shedding or damage to the asphalt matrix; the compatibilizer can promote the uniform dispersion of the components in the wear layer system, so that the surface of the wear layer forms a rich, regular and stable micro-rough texture, thereby improving the anti-slip performance.

[0009] Preferably, the compatibilizer is prepared by the following steps: The aminosilane coupling agent and linoleic acid are dispersed in toluene, and stirred to obtain a mixed dispersion; p-toluenesulfonic acid is added to the mixed dispersion, heated and stirred to react, cooled and allowed to stand for stratification, and separated to obtain an organic phase, and the organic phase is washed to obtain a washed organic phase; the washed organic phase is subjected to reduced pressure distillation to remove the solvent to obtain a compatibilizer.

[0010] The compatibilizer prepared according to the above steps can effectively improve the bonding performance, wear resistance and anti-slip performance of the wear layer.

[0011] Preferably, the raw materials for preparing the grafted modified lignin fiber include lignin fiber bulk and bis(β-cyanoethyl)amine.

[0012] Bis(β-cyanoethyl)amine contains cyano and amine groups. The cyano group gives the molecule rigidity and polarity, and the amine group has high reactivity. During the preparation process, the amine group undergoes grafting copolymerization with the abundant hydroxyl, carboxyl and other active groups on the lignin fiber. The modified lignin fiber is tightly connected to the asphalt through chemical bonds, which enhances the cohesive force of the asphalt matrix and makes its bonding with ceramic particles, powder and other components more stable. Under the impact of traffic loads, it effectively solves the problem of loose internal structure of the wear layer and improves the stability of the overall structure. The grafted lignin fiber has improved strength and toughness, and can work with ceramic particles to resist the continuous friction and extrusion caused by vehicle driving, reduce the material loss of the wear layer, and extend its service life. The grafted modified lignin fiber optimizes the rheological properties of the asphalt, so that the surface of the wear layer can form a more suitable micro-texture during molding, increase the friction contact area between the tire and the road surface, and thus improve the anti-skid performance.

[0013] Preferably, the mass ratio of the lignin fiber body to bis(β-cyanoethyl)amine is 1:(0.6-1).

[0014] The grafted modified lignin fiber prepared according to the above mass ratio can effectively improve the bonding performance, wear resistance and anti-slip performance of the wear layer.

[0015] Preferably, the raw materials for preparing the fluorine-modified epoxy resin include epoxy resin bulk and fluorine-containing acrylic acid.

[0016] The fluorine atoms in the fluorinated acrylic acid molecules have low surface energy, which gives them chemical inertness and hydrophobic properties. Fluorinated acrylic acid and epoxy resin undergo copolymerization reaction to introduce fluorine atoms into the epoxy resin molecular chain. The special properties of fluorine atoms enhance the affinity of epoxy resin with inorganic substances such as ceramic particles and powders, and can achieve close adsorption at the molecular level. At the same time, the fluorine-modified epoxy resin and the organic components in the modified decolorized asphalt form a more stable cross-linking structure, which improves the overall bonding strength of the wear layer, allowing it to maintain a close bond under complex traffic loads and changing environments, effectively preventing peeling and delamination. The tough network structure formed by the fluorine-modified epoxy resin has good wear resistance and can cooperate with ceramic particles to efficiently disperse external force impacts, reduce material loss, and extend the service life of the wear layer. The low surface energy characteristics brought by fluorinated acrylic acid cause the surface of the wear layer to form a microscopic hydrophobic, oleophobic and stable rough texture, which provides reliable friction for tires under wet or oily road conditions, ensures driving safety, and improves anti-skid performance.

[0017] Preferably, the raw materials for preparing the fluorine-containing acrylic acid include ethyl 4-formylbenzoate, perfluorooctyltriethoxysilane and malonic acid.

[0018] The aldehyde group of 4-formylbenzoic acid ethyl ester has high reactivity and can react with perfluorooctyl triethoxysilane and malonic acid to construct a fluorinated acrylic acid molecular structure and strengthen the molecular cohesion. The modified epoxy resin can be tightly connected with other organic matter in the wear layer to form multi-level chemical bonds, effectively improving the bonding performance; the benzene ring structure introduced by 4-formylbenzoic acid ethyl ester can enhance the cohesion and stability of the epoxy resin, so that it can better resist external force impact in the wear layer, strengthen the overall structural strength, and prevent the material from excessive deformation under vehicle load; perfluorooctyl triethoxysilane Triethoxysilane introduces the fluorine element, and its silaneoxy group is hydrolyzed and embedded in the molecular chain to introduce perfluorooctyl. The fluorine atom has the characteristic of low surface energy, which makes the fluorinated acrylic acid produce special intermolecular forces when it comes into contact with inorganic substances such as ceramic particles, thereby enhancing the bonding strength between the inorganic substance and the organic matrix. Its long carbon chain structure can cooperate with the benzene ring to regulate the flexibility and ductility of the resin, thereby improving the stability and wear resistance of the wear layer; the fluorinated acrylic acid promotes the formation of a regular and durable micro-texture on the surface of the wear layer, and can also ensure the anti-slip performance of the wear layer in humid or oily environments.

[0019] Preferably, the fluorinated acrylic acid is prepared by the following steps: Disperse 4-formylbenzoic acid ethyl ester and perfluorooctyltriethoxysilane in toluene, add potassium carbonate to obtain a reaction solution; heat the reaction solution with stirring and reflux for reaction, filter after cooling, wash the filtrate with water, and remove the solvent by rotary evaporation to obtain an intermediate product; disperse the intermediate product in tetrahydrofuran, add hydrochloric acid aqueous solution, heat and stir for reaction, after cooling, neutralize with saturated sodium bicarbonate solution, wash with water to obtain a washed product solution, dry the washed product solution with anhydrous sodium sulfate, and remove the solvent by rotary evaporation to obtain a second intermediate product; disperse the second intermediate product and malonic acid in pyridine, heat and stir for reaction, after cooling, add dilute hydrochloric acid aqueous solution to precipitate the product, filter and collect the precipitate, wash the precipitate with water until neutral, and dry to obtain fluorine-containing acrylic acid.

[0020] The fluorinated acrylic acid prepared according to the above steps can effectively improve the bonding performance, anti-slip performance and wear resistance of the wear layer.

[0021] Preferably, the mass ratio of the epoxy resin body to the fluorine-containing acrylic acid is 1:(0.2-0.3).

[0022] The fluorine-modified epoxy resin prepared according to the above mass ratio has low surface energy and can effectively improve the bonding performance, anti-slip performance and wear resistance of the wear layer.

[0023] In the second aspect, the present application provides a method for preparing an ultra-thin colored asphalt wear layer, using the following technical solution: A method for preparing a colored asphalt ultra-thin wearing layer comprises the following steps: Add a plasticizer and a diluent to the modified decolorized asphalt, stir to obtain a premixed asphalt; mix and stir the powder and the color powder to obtain a mixed powder; mix and stir the modified decolorized asphalt and ceramic particles to obtain a premix; add the mixed powder and the compatibilizer to the premix, stir to obtain an asphalt mixture; spread the asphalt mixture on the pavement base, and compact to obtain an ultra-thin colored asphalt wear layer.

[0024] The colored asphalt ultra-thin wear layer prepared according to the above steps has good adhesion and wear resistance, can maintain good working performance for a long time, effectively prevents peeling and delamination, and has a regular micro-texture on the surface, which can provide good anti-slip performance.

[0025] In summary, the present application includes at least one of the following beneficial technical effects: 1. Ceramic particles have high hardness and good wear resistance. They are evenly dispersed in the wear layer system. In the process of friction and rolling generated by continuous driving of vehicles, they effectively bear external impact, reduce the loss of the main structure of the wear layer, and extend the service life of the road surface. The rough surface of ceramic particles increases the friction between the road surface and the vehicle tires. The color powder, powder, etc. cooperate with the modified bleached asphalt to form a suitable micro-texture on the surface of the wear layer, which can provide reliable grip for vehicles in both dry and wet environments, effectively ensure driving safety, and improve the anti-skid performance of the wear layer. The grafted modified lignin fibers in the modified bleached asphalt are closely connected with the bleached asphalt through chemical bonding, physical adsorption, etc., which enhances the cohesion of the asphalt itself, so that the wear layer and the lower road surface or other contact interfaces form a stable bond, effectively preventing peeling and delamination under the repeated action of traffic loads and environmental factors. Fluorine-modified epoxy resin, with its excellent chemical activity, further optimizes the bonding force between asphalt and each component and improves the overall bonding strength.

[0026] 2. Bis(β-cyanoethyl)amine contains cyano and amine groups. The cyano group gives the molecule rigidity and polarity, and the amine group has high reactivity. During the preparation process, the amine group undergoes grafting copolymerization with the abundant hydroxyl, carboxyl and other active groups on the lignin fiber. The modified lignin fiber is tightly connected to the asphalt through chemical bonds, which enhances the cohesive force of the asphalt matrix and makes its bonding with ceramic particles, powder and other components more stable. Under the impact of traffic loads, it effectively solves the problem of loose internal structure of the wear layer and improves the stability of the overall structure. The grafted lignin fiber has improved strength and toughness, and can work with ceramic particles to resist the continuous friction and extrusion caused by vehicle driving, reduce the material loss of the wear layer, and extend its service life. The grafted modified lignin fiber optimizes the rheological properties of the asphalt, so that the surface of the wear layer can form a more suitable micro-texture during molding, increase the friction contact area between the tire and the road, and thus improve the anti-skid performance.

[0027] 3. The fluorine atoms in the fluorinated acrylic acid molecules have low surface energy, which gives them chemical inertness and hydrophobicity. Fluorinated acrylic acid and epoxy resin undergo copolymerization reaction to introduce fluorine atoms into the epoxy resin molecular chain. The special properties of fluorine atoms enhance the affinity between epoxy resin and inorganic substances such as ceramic particles and powders, and can achieve close adsorption at the molecular level. At the same time, the fluorine-modified epoxy resin and the organic components in the modified decolorized asphalt form a more stable cross-linking structure, which improves the overall bonding strength of the wear layer, allowing it to maintain a close bond under complex traffic loads and changing environments, effectively preventing peeling and delamination. The tough network structure formed by the fluorine-modified epoxy resin has good wear resistance and can cooperate with ceramic particles to efficiently disperse external force impacts, reduce material loss, and extend the service life of the wear layer. The low surface energy characteristics brought by fluorinated acrylic acid cause the surface of the wear layer to form a microscopic hydrophobic, oleophobic and stable rough texture, which provides reliable friction for tires under wet or oily road conditions, ensures driving safety, and improves anti-skid performance. DETAILED DESCRIPTION

[0028] The present application discloses a colored asphalt ultra-thin wear layer and a preparation method thereof. The raw materials used in the present application can be obtained from commercially available raw materials unless otherwise specified. The present application is further described in detail below in conjunction with the embodiments: Raw materials description: aminosilane coupling agent is γ-aminopropyltrimethoxysilane (CAS No.: 13822-56-5), linoleic acid (CAS No.: 60-33-3), p-toluenesulfonic acid (CAS No.: 104-15-4), lignin fiber is flocculent lignin fiber AF-XW-1, purchased from Tai'an Anfeng New Material Technology Co., Ltd., bis(β-cyanoethyl)amine (CAS No.: 111-94-4), ethyl 4-formylbenzoate (CAS No.: 6287-86-1), perfluorooctyltriethoxysilane (CAS No.: 51851-37-7), malonic acid (CAS No.: 141-82-2), epoxy The resin is E-51 (CAS No.: 61788-97-4), benzoyl peroxide (CAS No.: 94-36-0), the powder is limestone fine powder, the passing rate of 0.6mm square hole sieve is 100%, and the passing rate of 0.075mm square hole sieve is more than 80%, the particle size of ceramic particles is 1-2mm, the diluent is kerosene, the plasticizer is dibutyl phthalate (CAS No.: 84-74-2), acrylonitrile (CAS No.: 107-13-1), octyl triethoxy silane (CAS No.: 2943-75-1), ethyl formate (CAS No.: 109-94-4), acrylic acid (CAS No.: 79-10-7).

[0029] Example 1 Preparation of compatibilizer 3.85 kg of aminosilane coupling agent and 6.15 kg of linoleic acid were dispersed in 50 L of toluene, and stirred at a speed of 200 rpm to obtain a mixed dispersion; 0.5 kg of p-toluenesulfonic acid was added to the mixed dispersion, and the temperature was raised to 120° C. and stirred at a speed of 300 rpm for reaction for 6 hours. After cooling to below 30° C., the mixture was allowed to stand for stratification, and an organic phase was separated. The organic phase was washed three times with deionized water to obtain a washed organic phase; the washed organic phase was distilled under reduced pressure to remove the solvent to obtain a compatibilizer.

[0030] Preparation of grafted modified lignin fibers The lignin fiber was washed with deionized water and vacuum dried at 60°C to obtain pretreated lignin fiber; 3.13 kg of pretreated lignin fiber and 1.87 kg of bis(β-cyanoethyl)amine were mixed and dispersed in 10 L of anhydrous ethanol to obtain a modified dispersion; 50 g of potassium persulfate was dispersed in 0.5 L of deionized water to obtain an initiator solution; the potassium persulfate solution was added to the modified dispersion, and the temperature was raised to 80°C under a nitrogen atmosphere and stirred at 300 rpm for 6 hours. After cooling to 30°C, the modified lignin fiber was separated, washed with deionized water, and vacuum dried at 60°C to obtain a grafted modified lignin fiber.

[0031] Preparation of fluorine-modified epoxy resin 1.11 kg of ethyl 4-formylbenzoate and 4.53 kg of perfluorooctyltriethoxysilane were dispersed in 20 L of toluene, and 0.15 kg of potassium carbonate was added to obtain a reaction solution; the reaction solution was heated to 110°C, stirred at 300 rpm for reflux reaction for 5 h, and after cooling to 30°C, filtered, the filtrate was washed three times with deionized water, and the solvent was removed by rotary evaporation to obtain an intermediate product; the intermediate product was dispersed in 20 L of tetrahydrofuran, 0.2 L of 2 mol / L hydrochloric acid aqueous solution was added, the temperature was raised to 65°C, stirred at 250 rpm for 4 h, and cooled After the temperature reaches 30°C, the mixture is neutralized with a saturated sodium bicarbonate solution, washed three times with deionized water to obtain a washed product solution, dried with anhydrous sodium sulfate, and the solvent is removed by rotary evaporation to obtain a second intermediate product; the second intermediate product and 0.69 kg of malonic acid are dispersed in 20 L of pyridine, the temperature is raised to 120°C and stirred at 300 rpm for 5 hours, after cooling to 30°C, a 0.1 mol / L dilute hydrochloric acid aqueous solution is added to precipitate the product, the precipitate is collected by filtration, the precipitate is washed with deionized water until neutral, and vacuum dried at 60°C to obtain fluorinated acrylic acid.

[0032] 4.17 kg of epoxy resin, 0.83 kg of fluorinated acrylic acid and 0.1 kg of benzoyl peroxide were dispersed in 20 L of toluene, stirred at 300 rpm for 15 min, heated to 110° C. and reacted for 8 h. After cooling to 30° C., the solvent was removed by rotary evaporation to obtain a fluorine-modified epoxy resin.

[0033] Preparation of colored asphalt wearing course 7 kg of decolorized asphalt was stirred at 140°C at 150 rpm for 20 min to obtain molten asphalt, 1.5 kg of grafted modified lignin and 1 kg of fluorine-modified epoxy resin were added to the molten asphalt, and the mixture was stirred at 140°C at 200 rpm for 1 h to obtain modified decolorized asphalt; 6 kg of modified decolorized asphalt was taken, 0.2 kg of plasticizer and 0.5 kg of diluent were added, and the mixture was stirred at 145°C at 200 rpm for 30 min to obtain premixed asphalt.

[0034] Mix 42kg of powder and 5kg of color powder, and stir at a speed of 500rpm for 15min to obtain a mixed powder; mix the above-mentioned premixed asphalt and 35kg of ceramic particles, and stir at a speed of 300rpm for 25min to obtain a premix; add the mixed powder and 0.5kg of compatibilizer to the premix, and stir at a speed of 400rpm for 30min to obtain an asphalt mixture; spread the asphalt mixture on the road base, and compact it with a small vibratory roller to obtain an ultra-thin wear layer of colored asphalt.

[0035] Example 2 Preparation of compatibilizer 3.85 kg of aminosilane coupling agent and 6.15 kg of linoleic acid were dispersed in 50 L of toluene, and stirred at a speed of 200 rpm to obtain a mixed dispersion; 0.5 kg of p-toluenesulfonic acid was added to the mixed dispersion, and the temperature was raised to 120° C. and stirred at a speed of 300 rpm for reaction for 6 hours. After cooling to below 30° C., the mixture was allowed to stand for stratification, and an organic phase was separated. The organic phase was washed three times with deionized water to obtain a washed organic phase; the washed organic phase was distilled under reduced pressure to remove the solvent to obtain a compatibilizer.

[0036] Preparation of grafted modified lignin fibers The lignin fiber was washed with deionized water and vacuum dried at 60°C to obtain pretreated lignin fiber; 2.5 kg of pretreated lignin fiber and 2.5 kg of bis(β-cyanoethyl)amine were mixed and dispersed in 10 L of anhydrous ethanol to obtain a modified dispersion; 50 g of potassium persulfate was dispersed in 0.5 L of deionized water to obtain an initiator solution; the potassium persulfate solution was added to the modified dispersion, and the temperature was raised to 80°C under a nitrogen atmosphere, and the reaction was stirred at 300 rpm for 6 hours. After cooling to 30°C, the modified lignin fiber was separated, washed with deionized water, and vacuum dried at 60°C to obtain grafted modified lignin fiber.

[0037] Preparation of fluorine-modified epoxy resin 1.11 kg of ethyl 4-formylbenzoate and 4.53 kg of perfluorooctyltriethoxysilane were dispersed in 20 L of toluene, and 0.15 kg of potassium carbonate was added to obtain a reaction solution; the reaction solution was heated to 110°C, stirred at 300 rpm for reflux reaction for 5 h, and after cooling to 30°C, filtered, the filtrate was washed three times with deionized water, and the solvent was removed by rotary evaporation to obtain an intermediate product; the intermediate product was dispersed in 20 L of tetrahydrofuran, 0.2 L of 2 mol / L hydrochloric acid aqueous solution was added, the temperature was raised to 65°C, stirred at 250 rpm for 4 h, and cooled After the temperature reaches 30°C, the mixture is neutralized with a saturated sodium bicarbonate solution, washed three times with deionized water to obtain a washed product solution, dried with anhydrous sodium sulfate, and the solvent is removed by rotary evaporation to obtain a second intermediate product; the second intermediate product and 0.69 kg of malonic acid are dispersed in 20 L of pyridine, the temperature is raised to 120°C and stirred at 300 rpm for 5 hours, after cooling to 30°C, a 0.1 mol / L dilute hydrochloric acid aqueous solution is added to precipitate the product, the precipitate is collected by filtration, the precipitate is washed with deionized water until neutral, and vacuum dried at 60°C to obtain fluorinated acrylic acid.

[0038] 3.85 kg of epoxy resin, 1.15 kg of fluorinated acrylic acid and 0.1 kg of benzoyl peroxide were dispersed in 20 L of toluene, stirred at 300 rpm for 15 min, heated to 110° C. and reacted for 8 h. After cooling to 30° C., the solvent was removed by rotary evaporation to obtain a fluorine-modified epoxy resin.

[0039] Preparation of colored asphalt wearing course 7 kg of decolorized asphalt was stirred at 140°C at 150 rpm for 20 min to obtain molten asphalt, 1.5 kg of grafted modified lignin and 1 kg of fluorine-modified epoxy resin were added to the molten asphalt, and the mixture was stirred at 140°C at 200 rpm for 1 h to obtain modified decolorized asphalt; 7 kg of modified decolorized asphalt was taken, 0.5 kg of plasticizer and 1.5 kg of diluent were added, and the mixture was stirred at 145°C at 200 rpm for 30 min to obtain premixed asphalt.

[0040] Mix 60kg of powder and 8kg of color powder, stir at 500rpm for 15min to obtain a mixed powder; mix the above-mentioned premixed asphalt and 50kg of ceramic particles, stir at 300rpm for 25min to obtain a premix; add the mixed powder and 1.5kg of compatibilizer to the premix, stir at 400rpm for 30min to obtain an asphalt mixture; spread the asphalt mixture on the pavement base, compact it with a small vibratory roller, and obtain an ultra-thin colored asphalt wear layer.

[0041] Example 3 Preparation of compatibilizer 3.85 kg of aminosilane coupling agent and 6.15 kg of linoleic acid were dispersed in 50 L of toluene, and stirred at a speed of 200 rpm to obtain a mixed dispersion; 0.5 kg of p-toluenesulfonic acid was added to the mixed dispersion, and the temperature was raised to 120° C. and stirred at a speed of 300 rpm for reaction for 6 hours. After cooling to below 30° C., the mixture was allowed to stand for stratification, and an organic phase was separated. The organic phase was washed three times with deionized water to obtain a washed organic phase; the washed organic phase was distilled under reduced pressure to remove the solvent to obtain a compatibilizer.

[0042] Preparation of grafted modified lignin fibers The lignin fiber was washed with deionized water and vacuum dried at 60°C to obtain pretreated lignin fiber; 2.78 kg of pretreated lignin fiber and 2.22 kg of bis(β-cyanoethyl)amine were mixed and dispersed in 10 L of anhydrous ethanol to obtain a modified dispersion; 50 g of potassium persulfate was dispersed in 0.5 L of deionized water to obtain an initiator solution; the potassium persulfate solution was added to the modified dispersion, and the temperature was raised to 80°C under a nitrogen atmosphere and stirred at 300 rpm for 6 hours. After cooling to 30°C, the modified lignin fiber was separated, washed with deionized water, and vacuum dried at 60°C to obtain a grafted modified lignin fiber.

[0043] Preparation of fluorine-modified epoxy resin 1.11 kg of ethyl 4-formylbenzoate and 4.53 kg of perfluorooctyltriethoxysilane were dispersed in 20 L of toluene, and 0.15 kg of potassium carbonate was added to obtain a reaction solution; the reaction solution was heated to 110°C, stirred at 300 rpm for reflux reaction for 5 h, and after cooling to 30°C, filtered, the filtrate was washed three times with deionized water, and the solvent was removed by rotary evaporation to obtain an intermediate product; the intermediate product was dispersed in 20 L of tetrahydrofuran, 0.2 L of 2 mol / L hydrochloric acid aqueous solution was added, the temperature was raised to 65°C, stirred at 250 rpm for 4 h, and cooled After the temperature reaches 30°C, the mixture is neutralized with a saturated sodium bicarbonate solution, washed three times with deionized water to obtain a washed product solution, dried with anhydrous sodium sulfate, and the solvent is removed by rotary evaporation to obtain a second intermediate product; the second intermediate product and 0.69 kg of malonic acid are dispersed in 20 L of pyridine, the temperature is raised to 120°C and stirred at 300 rpm for 5 hours, after cooling to 30°C, a 0.1 mol / L dilute hydrochloric acid aqueous solution is added to precipitate the product, the precipitate is collected by filtration, the precipitate is washed with deionized water until neutral, and vacuum dried at 60°C to obtain fluorinated acrylic acid.

[0044] 4 kg of epoxy resin, 1 kg of fluorinated acrylic acid and 0.1 kg of benzoyl peroxide were dispersed in 20 L of toluene, stirred at 300 rpm for 15 min, heated to 110° C. and reacted for 8 h. After cooling to 30° C., the solvent was removed by rotary evaporation to obtain a fluorine-modified epoxy resin.

[0045] Preparation of colored asphalt wearing course 7 kg of decolorized asphalt was stirred at 140°C at 150 rpm for 20 min to obtain molten asphalt, 1.5 kg of grafted modified lignin and 1 kg of fluorine-modified epoxy resin were added to the molten asphalt, and the mixture was stirred at 140°C at 200 rpm for 1 h to obtain modified decolorized asphalt; 6.5 kg of modified decolorized asphalt was taken, 0.35 kg of plasticizer and 1 kg of diluent were added, and the mixture was stirred at 145°C at 200 rpm for 30 min to obtain premixed asphalt.

[0046] Mix 51kg of powder and 6.5kg of color powder, stir at 500rpm for 15min to obtain a mixed powder; mix the above-mentioned premixed asphalt and 42.5kg of ceramic particles, stir at 300rpm for 25min to obtain a premix; add the mixed powder and 1kg of compatibilizer to the premix, stir at 400rpm for 30min to obtain an asphalt mixture; spread the asphalt mixture on the pavement base, compact it with a small vibratory roller, and obtain an ultra-thin colored asphalt wear layer.

[0047] Example 4 Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in Example 4, the amount of lignin fiber used is 3.57 kg, and the amount of bis(β-cyanoethyl)amine used is 1.43 kg.

[0048] Example 5 Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, the amount of lignin fiber used is 2.27 kg, and the amount of bis(β-cyanoethyl)amine used is 2.73 kg.

[0049] Example 6 Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that in Example 6, bis(β-cyanoethyl)amine is replaced by acrylonitrile.

[0050] Example 7 Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that in Example 7, the amount of epoxy resin used is 4.55 kg, and the amount of fluorinated acrylic acid used is 0.45 kg.

[0051] Example 8 Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that in Example 8, the amount of epoxy resin used is 3.57 kg, and the amount of fluorinated acrylic acid used is 1.43 kg.

[0052] Example 9 Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that in Example 9, perfluorooctyltriethoxysilane is replaced by octyltriethoxysilane when preparing fluorinated acrylic acid.

[0053] Example 10 Example 10 is based on Example 3. The only difference between Example 10 and Example 3 is that in Example 10, ethyl 4-formylbenzoate is replaced by ethyl formate when preparing fluorinated acrylic acid.

[0054] Embodiment 11 Example 11 is based on Example 3. The only difference between Example 11 and Example 3 is that in Example 11, fluorine-containing acrylic acid is replaced by acrylic acid.

[0055] Comparative Example 1 Comparative Example 1 is based on Example 3, and the only difference between Comparative Example 1 and Example 3 is that the compatibilizer in Comparative Example 1 is replaced by an aminosilane coupling agent.

[0056] Comparative Example 2 Comparative Example 2 is based on Example 3, and the only difference between Comparative Example 2 and Example 3 is that in Comparative Example 2, the grafted modified lignin fiber is replaced by lignin fiber.

[0057] Comparative Example 3 Comparative Example 3 is based on Example 3, and the only difference between Comparative Example 3 and Example 3 is that in Comparative Example 3, the fluorine-modified epoxy resin is replaced by epoxy resin.

[0058] Performance testing (1) The "JTGE20-2011 Highway Engineering Asphalt and Asphalt Mixture Test Procedure" was selected as the standard. The asphalt mixture was spread on the base material and compacted to obtain the test specimen. The dynamic stability test was carried out. The dynamic stability was expressed by the number of times the wheel rolled when the rutting depth dropped by 1 mm. The greater the number, the better the dynamic stability of the specimen. Three specimens were prepared for each sample, and the average value was taken after measurement. The results are recorded in Table 1.

[0059] (2) Adhesion performance test: Spread the asphalt mixture on the base material and compact it to obtain a test piece. Apply tension to the test piece in a direction perpendicular to the bonding interface using a tensile testing machine at a tension rate of 5 mm / min. Record the maximum tension when failure occurs and calculate the bonding strength. Bond strength (MPa) = maximum tension (N) / bonding area (mm 2 ) Prepare three specimens for each sample, take the average value after measurement, and record the results in Table 1.

[0060] (3) The "JTG / D50-2017 Highway Asphalt Pavement Design Specification" was selected as the standard. The asphalt mixture was spread on the base material and compacted to obtain the test piece. The anti-skid performance of the test piece was tested with a pendulum friction meter. The surface pendulum value was tested. The larger the pendulum value, the better the anti-skid performance of the road surface. Each sample was tested three times, and the average value was taken after measurement. The results are recorded in Table 1.

[0061] Table 1 Test results of wear resistance, adhesion and anti-skid performance of ultra-thin colored asphalt wear layer Test results Dynamic stability (times / mm) Bond strength (MPa) Swing value (BPN) Example 1 5162 1.15 63 Example 2 5178 1.16 65 Example 3 5186 1.18 66 Example 4 5089 1.09 58 Example 5 5057 1.06 54 Example 6 5011 1.03 52 Example 7 5094 1.11 56 Example 8 5053 1.02 51 Example 9 4675 0.76 45 Example 10 4968 0.87 52 Embodiment 11 4381 0.69 42 Comparative Example 1 5032 1.08 56 Comparative Example 2 4864 0.92 50 Comparative Example 3 4108 0.53 40 It can be seen from Table 1 that the dynamic stability of Examples 1-3 is greater than 5162 times / mm, the bonding strength is greater than 1.15 MPa, and the swing value is greater than 63BPN, which shows that the colored asphalt ultra-thin wear layer prepared in the present application has good bonding properties, wear resistance and anti-slip properties.

[0062] As can be seen from Table 1, the only difference between Examples 4, 5, and 6 and Example 3 is that in Example 4, the mass ratio of lignin fiber to bis(β-cyanoethyl)amine is 1:0.4, in Example 5, the mass ratio of lignin fiber to bis(β-cyanoethyl)amine is 1:1.2, and in Example 6, bis(β-cyanoethyl)amine is replaced by acrylonitrile. Compared with Example 3, the adhesion, wear resistance and anti-skid properties of Examples 4, 5, and 6 are reduced; this is because the ratio of the components in the grafted modified lignin fiber is destroyed, and too much or too little bis(β-cyanoethyl)amine will affect the performance of the grafted modified lignin fiber, resulting in excessive modification and consumption of active groups on the lignin fiber or insufficient modification effect, thereby affecting its performance; bis(β-cyanoethyl)amine is replaced by acrylonitrile, and the steric hindrance of acrylonitrile is large, which affects the compatibility of the grafted modified lignin fiber with decolorized asphalt, thereby reducing the adhesion, wear resistance and anti-skid properties.

[0063] As can be seen from Table 1, the only difference between Examples 7 and 8 and Example 3 is that the mass ratio of epoxy resin to fluorinated acrylic acid in Example 7 is 1:0.1, and the mass ratio of epoxy resin to fluorinated acrylic acid in Example 8 is 1:0.4. Compared with Example 3, the adhesion, wear resistance and anti-slip properties of Examples 7 and 8 are reduced; this is because the ratio of epoxy resin to fluorinated acrylic acid is destroyed, and the introduction of too many or too few fluorine atoms will affect the intermolecular force of the system. Too strong a force will affect the compatibility of the fluorine-modified epoxy resin with other components, while insufficient introduction of fluorine atoms will have limited effect on reducing the surface energy, thereby limiting the performance improvement effect, and the adhesion, wear resistance and anti-slip properties of the wear layer are reduced.

[0064] As can be seen from Table 1, the only difference between Examples 9, 10, and 11 and Example 3 is that: in Example 9, perfluorooctyltriethoxysilane is replaced with octyltriethoxysilane when preparing fluorinated acrylic acid, in Example 10, 4-formylbenzoic acid ethyl ester is replaced with ethyl formate when preparing fluorinated acrylic acid, and in Example 11, fluorinated acrylic acid is replaced with acrylic acid. Compared with Example 3, the adhesion performance, wear resistance and anti-slip performance of Examples 9, 10, and 11 are reduced; this is because the synthetic components of fluorinated acrylic acid are replaced, the lack of fluorine element or the introduction of benzene ring, the modification effect on epoxy resin is reduced, and the performance is further reduced by replacing fluorinated acrylic acid with acrylic acid.

[0065] As can be seen from Table 1, the only difference between Comparative Example 1 and Example 3 is that the compatibilizer in Comparative Example 1 is replaced by an aminosilane coupling agent. Compared with Example 3, the adhesion performance, wear resistance and anti-slip performance of Comparative Example 1 are reduced. This is because the lack of the introduction of linoleic acid reduces the compatibility of the aminosilane coupling agent, and the regulating effect on the interface performance of the wear layer is reduced, thereby reducing the adhesion performance, wear resistance and anti-slip performance.

[0066] It can be seen from Table 1 that the only difference between Comparative Example 2 and Example 3 is that Comparative Example 2 replaces the grafted modified lignin fiber with lignin fiber. Compared with Example 3, the adhesion performance, wear resistance and anti-slip performance of Comparative Example 2 are reduced; this is because the lignin fiber lacks modification treatment, its compatibility and bonding strength with asphalt are reduced, and its regulating effect on the internal structure is weakened, so that the performance of the wear layer is reduced.

[0067] As can be seen from Table 1, the only difference between Comparative Example 3 and Example 3 is that the fluorine-modified epoxy resin is replaced by epoxy resin in Comparative Example 3. Compared with Example 3, the adhesion performance, wear resistance and anti-slip performance of Comparative Example 3 are greatly reduced; this is because the surface energy of the wear layer is increased due to the lack of modification treatment of fluorine-containing acrylic acid, the molecular structure lacks regulatory effect, the stability is reduced, and the adhesion performance, wear resistance and anti-slip performance are all affected.

[0068] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A colored asphalt ultra-thin wearing layer, characterized by: The raw materials for preparation include the following components in parts by weight: Ceramic particles 35-50 parts Color powder 5-8 parts Powder 42-60 parts Modified decolorized asphalt 6-7 parts Compatibilizer 0.5-1.5 parts Diluent 0.5-1.5 parts Plasticizer 0.2-0.5 parts The raw materials for preparing the modified decolorized asphalt include decolorized asphalt body, grafted modified lignin fiber and fluorine-modified epoxy resin.

2. The ultra-thin colored asphalt wearing layer according to claim 1, characterized in that: The raw materials for preparing the compatibilizer include aminosilane coupling agent and linoleic acid.

3. The ultra-thin colored asphalt wearing layer according to claim 2, characterized in that: The compatibilizer is prepared by the following steps: The aminosilane coupling agent and linoleic acid are dispersed in toluene, and stirred to obtain a mixed dispersion; p-toluenesulfonic acid is added to the mixed dispersion, heated and stirred to react, cooled and allowed to stand for stratification, and separated to obtain an organic phase, and the organic phase is washed to obtain a washed organic phase; the washed organic phase is subjected to reduced pressure distillation to remove the solvent to obtain a compatibilizer.

4. The ultra-thin colored asphalt wearing layer according to claim 1, characterized in that: The raw materials for preparing the grafted modified lignin fiber include lignin fiber body and bis(β-cyanoethyl)amine.

5. The ultra-thin colored asphalt wearing layer according to claim 4, characterized in that: The mass ratio of the lignin fiber body to bis(β-cyanoethyl)amine is 1:(0.6-1).

6. The ultra-thin colored asphalt wearing layer according to claim 1, characterized in that: The raw materials for preparing the fluorine-modified epoxy resin include epoxy resin body and fluorine-containing acrylic acid.

7. The ultra-thin colored asphalt wearing layer according to claim 6, characterized in that: The raw materials for preparing the fluorine-containing acrylic acid include ethyl 4-formylbenzoate, perfluorooctyl triethoxysilane and malonic acid.

8. The ultra-thin colored asphalt wearing layer according to claim 7, characterized in that: The fluorinated acrylic acid is prepared by the following steps: Dispersing ethyl 4-formylbenzoate and perfluorooctyltriethoxysilane in toluene, adding potassium carbonate to obtain a reaction solution; heating the reaction solution, stirring and refluxing for reaction, filtering after cooling, washing the filtrate with water, and removing the solvent by rotary evaporation to obtain an intermediate product; Dispersing the intermediate product in tetrahydrofuran, adding aqueous hydrochloric acid solution, heating and stirring to react, neutralizing with a saturated sodium bicarbonate solution after cooling, washing with water to obtain a washed product solution, drying the washed product solution with anhydrous sodium sulfate, and removing the solvent by rotary evaporation to obtain a second intermediate product; The second intermediate product and malonic acid are dispersed in pyridine, heated and stirred to react, and after cooling, a dilute hydrochloric acid aqueous solution is added to precipitate the product, and the precipitate is collected by filtration, washed with water until neutral, and dried to obtain fluorinated acrylic acid.

9. The ultra-thin colored asphalt wearing layer according to claim 8, characterized in that: The mass ratio of the epoxy resin body to the fluorine-containing acrylic acid is 1:(0.2-0.3).

10. A method for preparing an ultra-thin colored asphalt wearing layer as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: Adding a plasticizer and a diluent to the modified decolorized asphalt and stirring to obtain a premixed asphalt; Mixing and stirring the powder material and the color powder to obtain a mixed powder material; The modified decolorized asphalt and ceramic particles are mixed and stirred to obtain a premix; the mixed powder and the compatibilizer are added to the premix, and stirred to obtain an asphalt mixture; the asphalt mixture is spread on the road base, and compacted to obtain a colored asphalt ultra-thin wear layer.

Citation Information

Cited By

  • High-color-stability anti-flying gravel type open-graded colored asphalt wearing layer and preparation method thereof

    CN120817754A

  • Precast asphalt brick based on asphalt pavement milling material and preparation method thereof

    CN121824060A